2019
DOI: 10.1136/bmjopen-2019-031198
|View full text |Cite
|
Sign up to set email alerts
|

Overweight in Indonesia: an observational study of trends and risk factors among adults and children

Abstract: ObjectiveTo conduct a secondary data analysis detailing overweight prevalence and associations between key hypothesised determinants and overweight.DesignThis observational study used publicly available data from the Indonesian Family Life Survey (IFLS) (1993–2014). The IFLS is a home-based survey of adults and children that collected data on household characteristics (size, physical infrastructure, assets, food expenditures), as well as on individual-level educational attainment, occupation type, smoking stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
2
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 50 publications
5
66
2
6
Order By: Relevance
“…(2019), which is often regarded as indulgence and comfort food (Jack, O'Neill, Piacentini, & Schröder, 1997). Moreover, this finding is in agreement with Oddo, Maehara, and Rah (2019), who revealed that 65% of Indonesian adults consume fried snacks for 4 days/week, suggesting that they repeatedly consume food with a crispy texture. In the study of Sulistyawati et al.…”
Section: Resultssupporting
confidence: 92%
“…(2019), which is often regarded as indulgence and comfort food (Jack, O'Neill, Piacentini, & Schröder, 1997). Moreover, this finding is in agreement with Oddo, Maehara, and Rah (2019), who revealed that 65% of Indonesian adults consume fried snacks for 4 days/week, suggesting that they repeatedly consume food with a crispy texture. In the study of Sulistyawati et al.…”
Section: Resultssupporting
confidence: 92%
“…Based on the data collection, the respondents were in the normal category initially. (Oddo, Maehara, and Rah 2019), but they did not apply a healthy lifestyle (Pengpid and Peltzer 2017), and still lacked an understanding of the potential dangers of obesity that could threaten their future (Pengpid and Peltzer 2016). The results of this study were similar to another research using 2 methods, namely using an application using paper to rewrite what had been consumed for 24 hours (24h food recall).…”
Section: Discussionsupporting
confidence: 67%
“…It is likely that the Indonesian group considers dried mango only as a snack as also reported by Sulistyawati et al (2019), which is often regarded as indulgence and comfort food (Jack et al, 1997). Moreover, this finding is in agreement with Oddo, Maehara, & Rah (2019) who revealed that 65% of Indonesian adults consume fried snacks for 4 days/week, suggesting that they repeatedly consume food with a crispy texture. In the study of Sulistyawati et al (2019) some Indonesian participants reasoned eating dried fruit crisps was for enjoyment and then they preferred adding flavor enhancer.…”
Section: Utility Values For Different Levels Of Each Attribute Of Drisupporting
confidence: 92%